HUBUNGAN ANTARA SUPLEMENTASI VITAMIN A PADA IBU NIFAS DAN MORBIDITAS BAYI UMUR 0—6 BULAN DI KECAMATAN CIAMPEA, KABUPATEN BOGOR - Mei Rini Safitri; Dodik Briawan (Food and Nutrition Society of Indonesia, 2013)
The objective of this research was to analyze correlation between vitamin A supplementation among postpartum mothers and the morbidity of infant 0—6 month in Ciampea Sub-district. A cross sectional study of 56 subjects was conducted. The data collected in this study were breastfeeding practices, vitamin A supplementation, immunization and morbidity. The results showed that infants 0—6 months suffered from acute respiratory infection (ARI) 66.1%, fever (25.0%), diarrhea (14.3%), skin disease (7.1%), hepatitis B (3.6%), dengue fever (1.8%), and sprue (1.8%). There were a correlation between immunization and frequency/duration of hepatitis B; between the number of taking vitamin A supplement and incident of diseases as well as complementary feeding; complete immunization and duration of all illness (p<0.05). The logistic regression analysis showed that there were significant effects of complete immunization with duration of all illness (OR=0.110; 95%CI:0.013—0.940), and between number of taking vitamin A supplement with incident of diseases (OR=0.103; 95%CI:0.015—0.715).Keywords: